2016
DOI: 10.1080/23328940.2016.1184367
|View full text |Cite
|
Sign up to set email alerts
|

Periodizing heat acclimation in elite Laser sailors preparing for a world championship event in hot conditions

Abstract: Purpose: To examine the retention and re-acclimation responses during a periodized heat acclimation (HA) protocol in elite sailors preparing for the 2013 World Championships in Muscat, Oman (∼27–30°C, 40–60% RH). Methods: Two elite male Laser class sailors completed 5 consecutive days of HA (60 min per day in 35°C, 60% RH). Heat response tests (HRT) were performed on day 1 and 5 of HA, then 1 (decay 1, D1) and 2 (D2) weeks following HA. Participants were then re-acclimated (RA) for 2 days, within the next week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Laser and 470 classes) show a limited increase in T C , but a high performance decrement in the heat. Both Casadio and Corbett demonstrated the presence of inter-individual variation in the adaptive response to heat acclimation [26,27]. Furthermore, the thermophysiological responses to exercise in the heat was not related with baseline maximal VO 2 or previous exposure to a heat acclimation intervention [27].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Laser and 470 classes) show a limited increase in T C , but a high performance decrement in the heat. Both Casadio and Corbett demonstrated the presence of inter-individual variation in the adaptive response to heat acclimation [26,27]. Furthermore, the thermophysiological responses to exercise in the heat was not related with baseline maximal VO 2 or previous exposure to a heat acclimation intervention [27].…”
Section: Discussionmentioning
confidence: 97%
“…While the increased opportunity for cooling during upwind sailing may help to dissipate the greater metabolic heat production, a greater AWS is also likely to affect the work intensity when sailing and thereby resulting in a greater thermoregulatory burden [9]. To counteract these detrimental effects, Casadio and colleagues indicated that periodized heat acclimation did reduce heat strain in elite Laser sailors preparing for the 2013 World Championships [26].…”
Section: Discussionmentioning
confidence: 99%
“…These human adaptations to the increasing ambient temperatures can be attributed to multiple factors, such as physiological, behavioral, technological adaptations or changes in infrastructure (Hondula et al, 2015). Repeated heat exposures lead to physiological adaptations in heart rate, body core temperature and sweat rate that slowly decay (Daanen et al, 2018), and thus may lead to a more or less permanent state of heat acclimation (Casadio et al, 2016). In line with this, it has been shown that mortality is considerably higher in the heat waves early in summer when compared to successive heat waves, probably partly due to heat acclimation in the subjects that survived the initial heat waves (Kysely and Kriz, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The "partial acclimation" possessed by athletes allowed a short HA regimen, owing to higher baseline sweat rates versus sedentary individuals, and more rapid acclimation [41,42,46]. Discrepancy still surrounds optimal HA procedures, and rate of decay [41,47,48], which may be explored further in several extensive review articles [42][43][44]49]. GSL did increase in all participants throughout heat acclimation for a similar T core rise but was similar on days 5 and 6 (14.2 ± 2.3% increase on day 6 vs day 1), representing a classic hallmark of heat acclimation.…”
Section: Discussionmentioning
confidence: 99%